A organização do processo de trabalho na escola: uma crítica do trabalho pedagógico na formação do trabalhador em saúde - Travassos, Ronaldo dos Santos (2004)
This study is intended to approach the modifications in the organization of the process of work, which take place inside school due to the transformations in the world of work. Its main objective is to set out to investigate the changes in the organization of the pedagogical work and their implications in the technical and professional background of the workers in the field of health, because of the significant influence of capital on structuring the school direct or indirectly. This study also intends for studying the nature of school as an organization, highlighting the function of the specialists as a way of controlling the technical division in the organization of work in schools. It also highlights the ideological character of the pedagogical work responsible for the education of workers, who are meant to occupy different levels in the hierarchy of the capitalistic production by means of a correspondence between the social relations of production and the social relations of education. The conclusions indicate that the organization of schoolwork follows the principles of rationality and has a very well defined hierarchical structure. It emphasizes the culpability of school whenever it does not provide appropriate education for the workers. The pedagogical work points out to the ideological discourse of the specialized knowledge while exercising the functions in the educational system. Also, it focuses on the pedagogical work as a political act.